2020
DOI: 10.1002/ctm2.254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of plasma ctDNA features and dynamics in gastric cancer treated with HER2‐targeted therapies

Abstract: • Plasma ctDNA-based diagnosis was more sensitive than conventional computed tomography scanning in 40% of patients, gaining time for clinical management. • Plasma tumor mutation burden was a potential marker to predict the therapeutic outcomes of human epidermal growth factor receptor 2 (HER2)targeted therapy in GC. • HER2-positive patients with high TMB might gain more therapeutic benefits from immunotherapy instead of HER2-targeted regimens that required further studies and validations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Thus, there is an unmet clinical need for a biomarker that more accurately reflects therapeutic efficacy and dynamic changes during therapy. Liquid biopsy, particularly ctDNA from plasma, has high sensitivity and specificity in early cancer detection ( 34 ), so it may be useful for assessing dynamic changes in genes. Furthermore, because tumor tissue sequencing often relies on archival tissue obtained prior to the development of metastatic disease, ctDNA profiling may more readily facilitate the analysis of patients with metastatic disease by better capturing the presence of tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an unmet clinical need for a biomarker that more accurately reflects therapeutic efficacy and dynamic changes during therapy. Liquid biopsy, particularly ctDNA from plasma, has high sensitivity and specificity in early cancer detection ( 34 ), so it may be useful for assessing dynamic changes in genes. Furthermore, because tumor tissue sequencing often relies on archival tissue obtained prior to the development of metastatic disease, ctDNA profiling may more readily facilitate the analysis of patients with metastatic disease by better capturing the presence of tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In different stages of its development, different components and genes participate in it. It is very beneficial for us to study gastric cancer better by studying various genes, mechanisms, and components involved in the development of GC [15,16]. In recent years, many studies have confirmed that miRNA almost participates in all cell biological processes, such as cell development, cell proliferation and apoptosis, cell migration, and invasion [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ctDNA response could be used to evaluate therapeutic effect and to explore potential resistance mechanisms for targeted drugs (17,18). Considering the high heterogeneity characteristic of GC, ctDNA was used as an important tool for monitoring disease progression (19,20). The appearance of ctDNA could predict tumor recurrence earlier than routine imaging examination.…”
Section: Discussionmentioning
confidence: 99%